Coronary risk factor levels: differences between educational groups in 1972-87 in eastern Finland. Issue 2 (April 1995) - Pekkanen, J; Uutela, A; Valkonen, T; Vartiainen, E; Tuomilehto, J; Puska, P
Abstract : STUDY OBJECTIVE--To compare differences in coronary heart disease (CHD) risk factor levels between educational groups in the 1970s and 1980s in eastern Finland. DESIGN AND PARTICIPANTS--Independent, cross sectional population surveys were undertaken in 1972, 1977, 1982, and 1987 of randomly selected men and women aged 30-59 living in two provinces in eastern Finland. Altogether 20, 096 subjects participated. The lowest observed level of participation in either sex or province in any year was 77%. Serum cholesterol values and blood pressure measurements, body mass index, smoking, and the level of education were determined in each survey using comparable methodology. MAIN RESULTS--More poorly educated men and women had higher levels of all risk factors at the end of the study period (1987). There was no change between 1972 and 1987 in differences between educational groups in mean serum cholesterol values and the diastolic blood pressure level in either sex, and in smoking in men. In women, the proportion of smokers was highest in the better educated in the 1970s but lowest in this group in the 1980s (interaction between year of examination and educational level p < 0.01). Differences between educational groups in mean body mass index increased with time in both men (p < 0.001) and women (p = 0.06). CONCLUSIONS--Relative differences between socioeconomic groups in CHD mortality have increased in Finland in the 1970s and 1980s. Present results from eastern Finland show no reduction in differences between educational groups in risk factor levels, and even some evidence of increasing differences. Although a comparison between mortality trends and risk factor trends is problematic, trends in the risk factors analysed do not seem to be a major cause for the increasing differences in CHD mortality in Finland, at least in men. On the other hand, the risk factor trends analysed show no progress towards reducing inequalities in health, a major goal of public health policy.